Salvage chemotherapy in the intensive care unit: a case report of successful treatment of a critically ill patient with metastatic testicular germ cell tumor - Grela, Karol; Sobchynskyi, Mykola; Piȩtak, Mateusz; Kruczyk, Barbara; Domański, Piotr; Kucharz, Jakub; Symonides, Małgorzata; Demkow, Tomasz (Frontiers in Medicine, 2025)
Testicular cancer, predominant among young males, poses a significant healthcare challenge with varying incidence rates across European regions. Germ cell tumors (GCTs), constituting 95% of the cases, can be divided into seminoma and non-seminomatous germ cell tumors (NSGCTs). Metastases commonly occur in the lungs, lymph nodes, liver, bone, and brain. This study focuses on a 23-year-old with metastatic NSGCT, who underwent chemotherapy in an intensive care unit setting, followed by a remarkable improvement in his condition. The patient’s initial complaint was persistent abdominal pain, which led to a discovery of an extensive tumor in the abdominal cavity. He underwent cytoreductive surgery, and required admission to an intensive care unit (ICU) due to surgical complications. Histopathology identified a yolk sac tumor. Despite the serious condition, chemotherapy was started. The patient’s condition continued to deteriorate, requiring the initiation of mechanical ventilation. However, the multidisciplinary team opted for a continued treatment. Eventually, the AFP levels started to decrease and a gradual improvement of the patient’s condition have been observed. This allowed to a bleomycin, etoposide, and platinum regimen. Following a complex hospitalization and subsequent surgical resection of residual lesions, the patient remains in good clinical condition. Regular follow-up evaluations have revealed no evidence of disease recurrence. Although NSGCT is characterized by a rather favorable prognosis, it is a significant challenge to clinicians, as the diagnosis is often delayed due to the lack or low specificity of the symptoms. Despite the usually young age of the patients diagnosed with metastatic NSGCT, the patients condition can deteriorate rapidly, presenting with multiorgan failure and a need for an ICU treatment. However, the severity of the patients’ condition should not be unequivocally associated with being not suitable for a systemic curative treatment. Such patients can still benefit from the chemotherapy, and a cooperation between the oncologists and critical care physicians is crucial to improving the outcomes and increase the probability of recovery.